Home and hub: pet trade and traditional medicine impact reptile populations in source locations and destinations. Issue 1982 (14th September 2022) - Dufour, Pauline C.; Miot, Elliott F.; So, Tsz Chun; Tang, Shun Long; Jones, Emily E.; Kong, Tsz Ching; Yuan, Felix Landry; Sung, Yik-Hei; Dingle, Caroline; Bonebrake, Timothy C.
Abstract : The pet trade and Traditional Chinese Medicine (TCM) consumption are major drivers of global biodiversity loss. Tokay geckos ( Gekko gecko ) are among the most traded reptile species worldwide. In Hong Kong, pet and TCM markets sell tokay geckos while wild populations also persist. To clarify connections between trade sources and destinations, we compared genetics and stable isotopes of wild tokays in local and non-local populations to dried individuals from TCM markets across Hong Kong. We found that TCM tokays are likely not of local origin. Most wild tokays were related to individuals in South China, indicating a probable natural origin. However, two populations contained individuals more similar to distant populations, indicating pet trade origins. Our results highlight the complexity of wildlife trade impacts within trade hubs. Such trade dynamics complicate local legal regulation when endangered species are protected, but the same species might also be non-native and possibly damaging to the environment.